Situating Kazuo Ishiguro Within the Realms of Memory and Identity - Margaret L. Pachuau; C. Lalrinfeli (Asiatic: IIUM Journal of English Language and Literature, 2023)
This article focuses on components of memory and identity and their thematic centrality in Kazuo Ishiguro’s two novels namely, A Pale View of Hills (1982) and The Remains of the Day (1988). Ishiguro explores the complexities of memory in his novels, where distortion, suppression, and unreliability serve to define an individual’s identity through memory. Memory is a literary trope that Ishiguro has used repeatedly and diversely to enrich both his characters and plots. By examining how memories inform identity, this paper seeks to understand how our memories can affect our sense of self, and how this can shape our identity. The paper proposes that memories are not just simple recollections of events but are also complex narratives that are constructed from various sources. It argues that the interpretations of our memories can have a powerful effect on our sense of self and our identity.